Buckling of pre-twisted threads embedded in a soft matrix - Liow, Zhen Yi (Nanyang Technological University, 2023)
This Final Year Project seeks to find out the buckling effect of pre-twisted threads embedded in a soft matrix. A wire would be embedded into a polymeric matrix and compression loading would be applied onto the sample. The scope of this project includes silicone matrix of different hardness and the number of pre-twists of the nylon wire will be varied. Satisfactory results were obtained from this project it can be concluded that the pre-twisting the wires prior to compression loadings will be able to control the buckling behaviour.